Terrestrial alteration of Fe-Ni metals in Antarctic ordinary chondrites and the relationship to their terrestrial ages - Ikeda, Yukio; Kojima, Hideyasu (National Institute of Polar Research, 1991)
P(論文) Terrestrial alteration of Fe-Ni metals to limonites in ordinary chondrites is faster for kamacite than for taenite. H chondrites which have high ratios of kamacite/taenite alter more easily than LL chondrites which have the low ratios, L chondrites being intermediate. Qualitative weathering indices, A, B, and C, correspond to measured average alteration degrees (proportion of metal converted to limonite) of <5%, 10-20%, and >50%, respectively. The surfaces of chondritic meteorites show higher degrees in alteration of Fe-Ni metals than the interiors, although the difference in the degree is merely a factor of two. There is no correlation between the average alteration degrees and the terrestrial ages for H and L chondrites, but the average alteration degree seem to depend upon the degrees of impact shocks which the chondrites had suffered in or on the parent body. departmental bulletin paper